Current trends and the future of metamorphic malware detection - Alam, Shahid; Traoré, Issa; Soğukpinar, Ibrahim (Association for Computing Machinery, 2014)
Dynamic binary obfuscation or metamorphism is a technique where a malware never keeps the same sequence of opcodes in the memory. This stealthy mutation technique helps a malware evade detection by today's signature-based anti-malware programs. This paper analyzes the current trends, provides future directions and reasons about some of the basic characteristics of a system for providing real-time detection of metamorphic malware. Our emphasis is on the most recent advancements and the potentials available in metamorphic malware detection, so we only cover some of the major academic research efforts carried out, including and after, the year 2006. The paper not only serves as a collection of recent references and information for easy comparison and analysis, but also as a motivation for improving the current and developing new techniques for metamorphic malware detection. © 2021 Elsevier B.V., All rights reserved.
7th International Conference on Security of Information and Networks, SIN 2014 -- Glasgow; University of Glasgow -- 113072
Keywords: End point security; Malware detection; Metamorphic malware; Obfuscations